Evaporation of Droplets of Binary Mixtures of Lower Monohydric Alcohols in Heated Air - Kopiyka, O.K.; Kalinchak, V.V.; Chernenko, A.S. (Ukrainian Journal of Physics, 2023)
The results obtained while studying the evaporation process of single droplets of lower alcohols – ethanol, butanol, and their binary mixtures – with initial droplet sizes of 1.5–2.5 mm in heated air at the atmospheric pressure are reported. It is shown that the second inflection points in the time dependences of the temperature and the squared droplet diameter allow the evaporation time interval to be divided into two stages: 1) the simultaneous evaporation of both alcohols with a higher content of the more volatile alcohol and 2) the evaporation of the less volatile alcohol. The application of a thermocouple, which was heated in the oven under experimental conditions, diminished the droplet evaporation time and increased the stationary temperature of the droplet evaporation. At air temperatures higher than the boiling point of the liquid fuel, the temperature difference between the gaseous medium and the evaporating droplet surface depended linearly on the gaseous environment temperature. We propose a formula for calculating the evaporation temperature for a droplet of a binary solution in heated air, which allows estimating the temperature at which the quasi-stationary evaporation of the droplet begins provided a low rate of temperature growth. In the calculations, temperature dependence of the specific vaporization heats and the difference of the Lewis number from unit. The emphasis is made on the necessity of taking the Stefan flow into account when performing the physical and mathematical simulations.